ANALISIS POLA KESALAHAN MORFOLOGIS PADA SISWA DISGRAFIA KELAS IX SMPN 4 TAROGONG KIDUL DALAM PERSPEKTIF PSIKOLINGUISTIK - Halimah, Siti; Hasanah, Ninah; Loekman, Arief (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the patterns of morphological errors in the written language of a ninth-grade student at SMPN 4 Tarogong Kidul who is indicated to experience dysgraphia from a psycholinguistic perspective. The study was motivated by the observed discrepancy between the student's oral and written language abilities. Although the student demonstrates coherent and communicative oral expression, consistent and recurring morphological errors appear in written production. A descriptive qualitative approach with a single case study design was employed. Data were collected from the student's written works, including worksheets, class notes, and essay assignments, and were supported by classroom observation and interviews with the teacher and the student. Data were analyzed using Miles and Huberman's interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that morphological errors are the most dominant type, including phoneme omission, grapheme substitution, distortion of derived words, affixation errors (meN-, peN-, -an, kan), and inconsistency in complex word formation. These errors appear systematically and repeatedly across different writing tasks. From a psycholinguistic perspective, the errors indicate disruption at the translating stage of Hayes and Flower's writing process model, where linguistic ideas are converted into graphemic symbols. The student tends to rely more on the phonological route than on stable orthographic representations in the mental lexicon, suggesting weak morphological awareness and limitations in working memory capacity. The results suggest that the observed errors are not merely carelessness but reflect cognitive constraints in written language processing. This study contributes to applied psycholinguistic research and provides pedagogical implications for developing adaptive and inclusive writing instruction at the junior secondary level. Keywords: dysgraphia, morphological errors, psycholinguistics, writing process, affixation.